140 Lessons From the Front Line: Communication is Key. (16th March 2021) - Pyrke, B; Abdalla, B; Cartwright, G; Figg, K; Murphy, E; Tuck, A; White, H
Abstract: Introduction: As junior doctors, we very rarely receive formal teaching on communication after medical school, with telephone encounters and difficult conversations over technology being a vital yet missing part of our education. The COVID-19 pandemic has required us to adapt how we communicate with patients' families due to hospital visiting restrictions. In an era where tragically deterioration and death have been much more commonplace, we looked to identify areas where junior doctors felt their communication skills could be improved, and implemented a teaching programme to deliver this. Methods: Pre-teaching questionnaires were distributed to a range of grades of junior doctors working in University Hospital of Llandough, Cardiff. The questionnaires were distributed at the beginning of June 2020, after 3 months of working in pandemic conditions. A teaching session on telephone and video communication skills was delivered by a local palliative care consultant. Post-teaching, a repeat questionnaire was undertaken to assess response and identify key learning points. Results: Pre-teaching, 100% of the 22 respondents had had to participate in difficult conversations over the phone, 82% had had no formal phone based communication skills training and 81.82% felt some form of formal teaching would be helpful. Post-teaching, 12 junior doctors provided feedback with an average 37% increase in confidence to undertake difficult conversations. Key learning points from the session highlighted the importance of preparation, regularly updating the family to build trust and rapport, and integrating family updates via tele-communication into daily ward life. Conclusions: Education around telephone communication skills is critical to enable us to adapt our skills in accordance with the demands of the pandemic, to continue to support relatives and to engage with technology with confidence. Increased preparation is required to navigate difficult conversations via technology, and successful communication requires clinicians to take responsibility for initiating regular family updates.